SEG Technical Program Expanded Abstracts 2010 2010
DOI: 10.1190/1.3513161
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of converted‐wave extended images for migration velocity analysis

Abstract: Converted-wave data have been recognized to have potential in complementing conventional compressional data. However, imaging for converted-waves is more difficult mainly due to the need for estimating shear-wave velocities, in addition to compressional-wave velocities. The common practice is to obtain the shear-wave velocity by registering PS and PP images. Despite its low cost, this procedure is prone to error due to the assumption of imaging simple structure and due to the high potential for cycle skipping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Using our new extrapolation method, we would therefore expect similar improvements in elastic media. Moreover, because the penalty function usually defined for migration velocity analysis of elastic waves (Yan and Sava, 2010), which exploits the information contained in the extended images to invert for the velocity model, does not take into account the artificial events resulting from the vectorial extrapolation step, the inversion process could also benefit significantly from this new extrapolation procedure. However, although our new wavefield extrapolation procedure improves the elastic image, the receiver wavefields still show some nonphysical waves at early times (e.g., before a scattering event occurs -see Figure 5c -time 1) and partial wavefronts at later times (e.g., after a scattering event occurs -see Figure 5c times 3-5).…”
Section: Ravasi and Curtismentioning
confidence: 99%
“…Using our new extrapolation method, we would therefore expect similar improvements in elastic media. Moreover, because the penalty function usually defined for migration velocity analysis of elastic waves (Yan and Sava, 2010), which exploits the information contained in the extended images to invert for the velocity model, does not take into account the artificial events resulting from the vectorial extrapolation step, the inversion process could also benefit significantly from this new extrapolation procedure. However, although our new wavefield extrapolation procedure improves the elastic image, the receiver wavefields still show some nonphysical waves at early times (e.g., before a scattering event occurs -see Figure 5c -time 1) and partial wavefronts at later times (e.g., after a scattering event occurs -see Figure 5c times 3-5).…”
Section: Ravasi and Curtismentioning
confidence: 99%
“…In practice, migration and the velocity model building are more robust and easier in the depth domain for structurally complex environments (Liu et al, 2007). Recently, Yan and Sava (2010) conducted MVA in the depth domain for inverting the S-wave velocity model using PS data only. Rosales et al (2008) suggested to make use of PS CIGs in the depth domain to update both the P-and S-wave velocity models.…”
Section: Introductionmentioning
confidence: 99%
“…However, they use a Kirchoffbased migration, which is likely to break down in complex structures. Yan and Sava (2010) present a wave-equation migration velocity analysis (WEMVA) method that finds the S-wave velocities and P-S depth-migration images simultaneously, but the computation of elastic angle gathers is expensive. Moreover, the method does not impose any constraint on the proximity of P-S to P-P images.…”
Section: Introductionmentioning
confidence: 99%